Overview of Finger Millet (Eleusine coracana L.) Breeding and Prospects in Ethiopia: A Review - Berie, Abunu Marefia; Abate, Alemu (Department of Agronomy and Horticulture, IPB University, 2025)
The world has faced challenges to produce more food to feed the growing population. Improved crop varieties key inputs for significant increases in production and productivity. Finger millet is thus one of a highly nutritious and food security crop. In Ethiopia, major achievements were made for major crops; however, the time and resources devoted to improving finger millet are low compared to other cereal crops. As a result, there is little scientific intervention aimed at improving finger millet. Besides, the crop is constrained by biotic, abiotic, and socioeconomic factors. As a result, the productivity of finger millet is far below its potential. Nowadays, there is an initiation and effort to develop improved finger millet varieties; hence, yield increases have been achieved in Ethiopia over the years. The available genetic resources, wide adaptability of the crop, and the current growing acreage have at times been considered opportunities to boost crop production and productivity. Strong research efforts and the transfer of technologies have to be strengthened in the country, and such efforts must be made in finger millet potential areas of the country. Thus, to lift the value as an alternative food crop capitalizing on these opportunities could ensure food and nutrition security in Ethiopia and the world. Therefore, the objective of this study was to review and document information on the breeding achievements made, as well as key challenges, opportunities, and interventions, to provide insight into the future of finger millet breeding in Ethiopia.